Bigámia nászajándékba: Samuel Spillenberger nászéneke Máriássy János és Palugyay Zsófia esküvőjére (1635) - Máté, Ágnes (Antikvitás & Reneszánsz, 2019)
The present article discusses a set of poems registered in print nr. 1620 of the Régi Magyarországi Nyomtatványok catalogue. The poem was dedicated by a doctor of medicine from Levoča, Samuel Spillenberger to his alleged godson, the nobleman János Máriássy. Spillenberger wrote three poems in the name of each married brothers of Máriássy. The second poem, allegedly sang by Máriássy’s youngest brother, András, tells a story about a bigamist crusader from the 12th century. After presenting the family backgrounds of both the author and the addressees, the paper sheds light on the origin and possible sources of the story. Pointing out some specific textual properties of Spillenberger’s poem, the paper tries to trace down its exact source. It also offers a panoramic picture about the presence of the bigamist figure in German neo-Latin Literature and culture from the 16th to the 19th century. Finally, the article closes with some remarks about the position of the poem in its own literary context of seventeenth-century neo-Latin wedding poetry in Hungary.